Oral administration of Moringa oleifera oil but not coconut oil prevents mercury‐induced testicular toxicity in rats. (13th April 2016) - Abarikwu, S. O.; Benjamin, S.; Ebah, S. G.; Obilor, G.; Agbam, G.
Summary: This study was conducted to compare the effects of administration of coconut oil (CO) and Moringa oleifera oil (MO) on testicular oxidative stress, sperm quality and steroidogenesis parameters in rats treated with mercury chloride (HgCl2 ). After 15 days of oral administration of CO (2 ml kg −1 body weight) and MO (2 ml kg −1 body weight) along with intraperitoneal (i.p.) administration of HgCl2 (5 mg kg −1 body weight) alone or in combination, we found that CO treatment did not protect against HgCl2 ‐induced poor sperm quality (motility, count) as well as decreased testosterone level and 17β‐hydroxysteroid dehydrogenase (17β‐HSD) activity. Treatment with CO alone decreased glutathione (GSH), and glutathione peroxidase (GSH‐Px) activities and increased malondialdehyde (MDA) level in rat's testis, whereas MO did not change these parameters. Cotreatment with MO prevented HgCl2 ‐induced testicular catalase (CAT) and superoxide dismutase (SOD) activities, poor sperm quality and low testosterone level and also blocks the adverse effect of CO+HgCl2 (2 ml kg −1 body weight + 5 mg kg −1 body weight) on the investigated endpoints. In conclusion, MO and not CO decreased the deleterious effects of HgCl2 on sperm quality and steroidogenesis in rats and also strengthen the antioxidant defence of the testes. Therefore, MO is beneficial as an antioxidant in HgCl2 ‐induced oxidative damage.